CREATIVE AND INNOVATIVE LEARNING METHODS FOR EARLY CHILDHOOD EDUCATION TEACHER IN TKM NU 114 MUTTABIUL HUDA - Sri Nurhidayah; Alfina Citrasukmawati (Universitas Galuh, 2022)
Creative and innovative learning is significant to create a maximum learning process, especially for young age children. Children under 7 years old require a lot of attention to optimize their growth and development. This effort must be in line with teacher’s competency in learning process. Teachers at TKM NU 114 Muttabiul Huda Gresik still need a lot of good support system to improve their competency in developing creative and innovative learning. The problems are having low motivation, minimum management of institutions, unclear vision and mission to create new ideas and enhance new things. These are the background to carry out community service with partner, TKM NU 114 Muttabiul Huda. This service aims to improve the competency of teachers in the learning process with creative and innovative methods. Implementation is carried out through three stages, namely the preparation stage which includes discussion and observation activities. The second stage of implementation is in the form of training and the third stage is an evaluation with a questionnaire instrument. The results of this service are very significantly beneficial for teachers. First, teachers are more skillful at carrying out creative learning processes that were previously monotonous, boring and still focused on teacher centered. Second, the teachers understand the accurate method to be applied in learning process and can find the right problems solution in the classroom. Third, the teachers are more enthusiastic and open minded. In other words, the training in this community service develops teacher’s competency in teaching activity.